Aphid polyphenisms: trans-generational developmental regulation through viviparity - Ogawa, Kota; Miura, Toru (Frontiers in Physiology, 2014)
Polyphenism, in which multiple discrete phenotypes develop from a single genotype, is considered to have contributed to the evolutionary success of aphids. Of the various polyphenisms observed in the complex life cycle of aphids, the reproductive and wing polyphenisms seen in most aphid species are conspicuous. In reproductive polyphenism, the reproductive modes can change between viviparous parthenogenesis and sexual reproduction in response to the photoperiod. Under short-day conditions in autumn, sexual morphs (males and oviparous females) are produced parthenogenetically. Winged polyphenism is observed in viviparous generations during summer, when winged or wingless (flightless) aphids are produced depending on a variety of environmental conditions (e.g. density, predators). Here, we review the physiological mechanisms underlying reproductive and wing polyphenism in aphids. In reproductive polyphenism, morph determination (male, oviparous or viviparous female) within mother aphids is regulated by juvenile hormone (JH) titers in the mothers. In wing polyphenism, although JH is considered to play an important role in phenotype determination (winged or wingless), the role is still controversial. In both cases, the acquisition of viviparity in Aphididae is considered to be the basis for maternal regulation of these polyphenisms, and through which environmental cues can be transferred to developing embryos through the physiological state of the mother. Although the mechanisms by which mothers alter the developmental programs of their progeny have not yet been clarified, continued developments in molecular biology will likely unravel these questions.